A method of bedside urethrography before catheterization in pelvic trauma in Korea: a case report - Hojun Lee; Sung Yub Jeong; Kun Hwang (Journal of Trauma and Injury)
We introduce a convenient method of urethrography before catheterization for patients with pelvic trauma that can be used in a resuscitation area. A 10-mL syringe without a needle was used. X-ray contrast medium (Iohexol, 300 mg I/mL) was administered through the urethral orifice using a 10-mL syringe without needle and a simple pelvic anteroposterior film was taken (70 kilovolt [peak], 50 mAs). A 36-year-old soldier with a saddle injury from a gun barrel was taken to a trauma center. He had a pelvic fracture and complained of hematuria. Bedside urethrography above described was performed. The anterior urethra showed nonspecific findings, but dye leaked from the posterior urethra. Bedside Foley catheter insertion was attempted, but the catheter could not be advanced past the membranous urethra. Thereafter, suprapubic catheterization was performed. On the day of the injury, iliac artery embolization was carried out. The dislocated sacroiliac joint was also treated using open reduction and internal fixation. On hospital day 7, guidewire Foley insertion was performed. This bedside urethrography technique is simple and useful for pelvic fractures in which urethral injury is suspected.